The influence of physical activity on the mood of people subjected to standard rehabilitation after cardiac surgery - Boćkowski, Radosław; Kotowska, Joanna; Szylińska, Aleksandra; Turoń-Skrzypińska, Agnieszka; Rotter, Iwona (Journal of Education, Health and Sport, 2019)
Introduction: The aim of this study was to assess the correlation between standard post-operational early rehabilitation and compare the differences between mood before and after rehabilitation. Materials and methods: 51 people were examined. The study group included patients from the Department of Cardiac Surgery, SPSK No. 2, PUM in Szczecin. The data was collected using a standardized UMACL scale and an original survey to collect basic data. On the UMACL scale, there are three mood determinants: Hedonic Tone (HT), Tense Arousal (TA) and Energy Arousal (EA). A high level of Hedonic Tone and Energy Arousal as well as low Tense Arousal are considered a good mood. The respondents first filled the UMACL scale questionnaire, then proceeded to a 10-minute drive on the rotor. After completing physical activity, they again completed the same UMACL scale. The obtained results were subjected to statistical analysis. Results: Energy Arousal and Hedonic Tone values increased, and Tense Arousal values decreased in post-operative patients. Conclusions: Even short, one-off physical activity has a positive effect on the mood in cardiac surgery patients.